Moral Foundations for the Feelings of Shame and Pride Regarding the Native Country - Oleg A. Sychev; Timofei A. Nestik (Peoples' Friendship University of Russia (RUDN University), 2022)
The feelings of shame and pride regarding the native country are important in the context of the problem of civic identity; therefore, they are of growing interest on the part of sociologists and psychologists. Given the moral nature of these emotions, their analysis based on one of the most authoritative approaches in the psychology of morality, moral foundations theory, seems relevant and justified. The purpose of this study was to analyze the moral foundations for the feelings of shame and pride regarding the native country. The online survey involved 752 subjects (49.9% men) aged 16-73 (mean age M = 42, SD = 10.87). A new version of the Moral Foundations Questionnaire (MFQ-2) was used to assess the moral foundations. The feelings of shame and pride regarding the native country were assessed using a questionnaire tested in previous sociological and psychological studies. Data processing was carried out using exploratory factor analysis, linear regression analysis and analysis of variance (ANOVA). The results of the regression analysis on the factors of shame and pride regarding the native country showed that the moral foundations play an important role in these feelings among the inhabitants of Russia. However, a specific set of predictors is determined by what exactly is the subject of pride or shame. In general, the moral foundations of loyalty and authority are of the greatest importance for pride, while liberty and equity are most important for shame regarding the native country. Using the latent profile analysis, we identified typical profiles of moral foundations associated with age. A small group (14% of the sample) of relatively young respondents with an individualistic profile of moral foundations demonstrated a significant predominance of shame over pride regarding their native country. The other two groups with a traditionalist and a moderate profiles of moral foundations were characterized by a balance (or approximate equality) of pride and shame regarding their native country. The results of the study contribute to a deeper understanding of the role of the moral factors of patriotic education based on the formation of a feeling of pride in the country.